Utilization of Golden Snail (Pomacea canaliculata) for Growth and Stimulate Color of Red Melon Discus Fish Juvenile (Symphysodon aequifasciata) - Wahyu Suryadi; Sukarman Sukarman; Mustahal Mustahal; Mas Bayu Syamsunarno (JURNAL PERIKANAN DAN KELAUTAN, 2019)
Golden snail contains high protein and carotenoids. Red melon discus fish requires high protein for growth and can be used for enhancing color. The purpose of this study was to evaluate the use of golden snail as a substitution of silkworms to increase growth and stimulate the color of red melon discus fish. The experiment used Completely Randomized Design (CRD) with 5 treatments and 3 replications. The treatments are 100% silk worm (A), 75% silkworm + 25% golden snail (B), 50% silkworm + 50% golden snail (C), 25% silkworm + 75% golden snail (D), and 100% golden snail (E). After acclimated, red melon discus fish of 0.32 ± 0.16 g and 2.41±0.02 cm in average weight and length were randomly stocked in 15 aquaria of 40x30x35 cm3 in dimension size containing 30 L water at 10 fingerlings/aquarium and given feed test as much as 5% body weight with frequency of 2 times a day for 56 days of the experimental period. The parameters that observed is survival rate, absolute weight, absolute growth, feed consumption and color. The results showed that high level of golden snail caused declining growth performance of red melon discus fish (P<0.05) and does not affect the color of discus fish (P>0.05) but can improve color quality during the experimental period. Substitution of golden snail to silkworm as much as 25% resulted in the highest growth performance and stimulate color of red melon discus fish.